Tingkat Kepatuhan Pajak Freelancer: Studi Deskriptif pada Pekerja Kreatif di Sukabumi - Nurlela, Siti; Zulkarnain, Zulkarnain (Cakrawala Repositori IMWI, 2025)
This study analyzes the level of tax compliance among freelancers, focusing on four key indicators: tax payment compliance, tax reporting compliance, compliance with overdue tax obligations, and tax legal compliance. Data were collected through an online questionnaire from respondents working as freelancers (including content creators, photographers, MCs, and wedding organizers) in Sukabumi. The research findings indicate that freelancers generally exhibit a good to very good level of tax compliance across all indicators. The average scores for tax payment compliance, tax reporting compliance, and compliance with overdue obligations were all 72.67%, while tax legal compliance reached 80.00%. These findings suggest adequate awareness and practices in fulfilling tax obligations among the majority of freelancers. However, further analysis revealed variations in compliance levels and interesting gender differences. Males showed slightly higher scores in payment and reporting compliance, while females scored slightly higher in compliance with overdue obligations. Tax legal compliance showed equally high scores for both genders, although there was an indication of a minority of female respondents with a history of tax-related criminal offenses. This study concludes that while freelancer tax compliance is generally positive, there is a need for more specific and gender-responsive tax socialization. It is recommended that tax authorities enhance educational programs focusing on financial literacy, ease of access to digital platforms, and tailored communication strategies for each gender, to strengthen the consistency and quality of tax compliance in the future.